A longitudinal prospective study: The effect of annual seasonal transition and coaching influence on aerobic capacity and body composition in division I female soccer players - Purdom, T. M.; Levers, K. S.; McPherson, C. S.; Giles, J.; Brown, L. (Sports, 2020)
This study assessed how seasonal transitions and coaching influence affect aerobic capacity (AC) and body composition across the annual training cycle (ATC). Eleven division 1 female soccer players were tested after five predesignated time blocks (B1-B5): post-season 2016 (B1), nine-week transition (B2), spring season (B3), pre-season (B4), and post-season 2017 (B5). Height, weight, and body composition (fat-free mass (FFM)) were measured prior to a standardized 5 min treadmill running and dynamic movement warm up before a maximal AC test. Statistical analysis included a 4 × 5 repeated-measures analysis of variance (ANOVA) (dependent variable × time) with the Fishers Least Significant Difference (LSD) post-hoc test when relevant; data are presented as mean ± standard deviation, effect size (ES), and percent change (%). The statistical analysis revealed that the ATC had a significant main effect on AC and FFM (F3,4 2.81, p = 0.001; Eta2 = 0.22). There were significant increases in AC across the transition period (B1-B2) with reduced training volume (Delta + 12.9%, p = 0.001; ES = 0.50) while AC and FFM peaked after the spring season with directed concurrent training paired with adequate rest B1-B3 (Delta + 16.4%, p < 0.01; ES = 0.81). AC decreased across the pre-season with indirect training (B3-B4) (Delta? - 7.0%, p = 0.02; ES = 0.50) and remained suppressed without change (p > 0.05) across the competitive season (B4-B5). Rest, concurrent training, and directed training positively affected AC, while indirect training and high training loads with little rest negatively affected AC.